Upaya Relasional dan Outcome Relasional dalam Membangun Retensi Pelanggan pada Peritel - Utami, Christina Whidya (Jurnal Widya Manajemen & Akuntansi, 2006)
This research tries to elaborate how the relationship trough relationship outcomes in hypermarket and warehouse store can influence the customer retention. The research sample was shoppers in hypermarket and warehouse store in Surabaya which run relationship efforts' such as Carrefour, Makro, Alfa, Indogrosir and Hypermart. :, " This research proves that the perception o/'customer relationship e/forts influences the relationship outcomes which in turn affect the customer retention. tn addition this study has some practical implications such as: (11 the relationship effort strategy (2) the relationship outcomes; (3) the customer retention and (4) propose a new conceptual framework.